(untitled) (Nexo Revista Científica, 2023)
This research aims to use green practices to attain sustained performance. To apply that, an important question is rising, which is, how does GSCMP affect achieve sustained performance via green technology as an intermediate variable? the General Company for Electrical and Electronic Industries in Baghdad is chosen as a field to study the impact of these variables. The research community was represented by the employees of the researched company, and a purposive sample was chosen, which consisted of the administrative leaders, and a total of 221 individuals. To examine the validity of our supposed hypotheses, the related attitudes data of the respondents were collected through the questionnaire form and analyzed based on ready-made software such as SPSS Ver 21, and AMOS 24. Our model reached different results, the most remarkable one is that the substantial direct and indirect outcomes between the research variables. Accordingly, we have come up with some important recommendations, a significant one is that the management of the considered company should pay more attention to GSCMP and the application of green technology because of their prominent role in achieving sustained performance.